"Entre encantados e outras criaturas sobrenaturais": A identidade linguístico-cultural híbrida do Brasil e da Argentina em narrativas orais - Figueira-Cardoso, Samuel (2022)
Oral narratives are present in all known cultures. In Latin America, cultures and peoples are mestizos, hybrids, born of centuries of influence and linguistic and cultural imposition of European colonizers and contact with different population contingents. The paper aims to discuss the oral narratives affiliated with the legendary Argentine and Brazilian as socio-communicative practices that reveal this hybrid identity, which as such must be understood as a constitutive part of the cultural identity of the speakers who produce them. To this end, we anchor ourselves to language and cultural studies that advocate an interactive and socio-historically situated notion of language and reflections on narration, identity, and fictional discourse. At the same time, we seek to build a path that allows the discussion of some concepts that we consider relevant to this study. The methodology adopted is of a qualitative nature of an interpretive nature, having as the object of analysis oral and written narratives taken from two corpora, one collected on the urban peripheries of Buenos Aires and the other in the interior of Santarém, Pará, Brazil.